Liquidity Analysis Of Bumdes Plantation Turangi Bahorok District Langkat District - Isfahani, Faradibael; Herlina, Sri (Institute for Law and Economics Studies, 2025)
The Village-Owned Enterprise (BUMDes) of Turangi Plantation is a government initiative to improve the economy and welfare of village communities. However, after five years of establishment, BUMDes in Bahorok Sub-district, including Turangi, are facing challenges in their development. The businesses managed are still limited to savings and loans and sales of agricultural materials with minimal capital. This study aims to analyze the liquidity and performance of BUMDes Turangi, and identify the constraints faced. The method used is descriptive quantitative approach, analyzing financial statements and involving interviews and observations. The results show that the liquidity of BUMDes Turangi is low, reflected in the current and quick ratios that do not meet the ideal standard. Its performance is also not optimal, with minimal revenue and profit. Constraints include an unprofessional managerial system, limited capital, lack of information, and the absence of a clear vision and mission. Recommendations for improvement include: (1) managerial training for managers; (2) business diversification; (3) improved access to financing; (4) improved transparency of financial management; (5) development of a long-term vision and plan. Hopefully, the implementation of these recommendations can improve the liquidity and performance of BUMDes, as well as improve the welfare of village communities.